The Simplified Tax System as a Strategic Option to Mobilizing Financial Resources: Souk Ahras Province Local Tax Center Case Study - Atamnia, Amina; Boughalem, Zineb (Journal of Ecohumanism, 2025)
This study attempts to shed light on the simplified tax system applied in Algeria, i.e., the Single Fixed Tax (IFU) system, and determine its role in the state's financial resource development and mobilization. This is achieved by applying the analytical case study method to the local tax center of Souk Ahras province for the years 2022–2025.The study reached some principal conclusions, the most important of which is that the simplified tax system plays an essential role in creating a healthy environment that facilitates and simplifies the processes of tax declaration for taxpayers. This greatly affects the mobilization of the state's financial resources. However, the operation of tax collection in the local tax center of Souk Ahras is still run using traditional methods during the research period. This calls for more efforts by the Algerian public authorities to fully computerize the tax sector, modernize tax collection mechanisms, and migrate to electronic payment systems in all local tax centers nationwide